2011
DOI: 10.1371/journal.pone.0017337
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Conditional Probability of Chord Progression on Brain Response: An MEG Study

Abstract: BackgroundRecent electrophysiological and neuroimaging studies have explored how and where musical syntax in Western music is processed in the human brain. An inappropriate chord progression elicits an event-related potential (ERP) component called an early right anterior negativity (ERAN) or simply an early anterior negativity (EAN) in an early stage of processing the musical syntax. Though the possible underlying mechanism of the EAN is assumed to be probabilistic learning, the effect of the probability of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 54 publications
5
59
1
Order By: Relevance
“…The brain of an acculturated listener listening to a melody or a sentence is sensitive to how it will probably unfold. This is manifest in the fact that events violating reasonable expectation elicit strong neural responses (Dien et al, 2003;James et al, 2008;Vuust et al, 2009;Pearce et al, 2010;Kim et al, 2011). The ability of the brain to detect and respond to improbable events is thought to depend not only on mastery of complex rules that govern the event stream but also on the encoding of simple statistical relations (Aslin and Newport, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The brain of an acculturated listener listening to a melody or a sentence is sensitive to how it will probably unfold. This is manifest in the fact that events violating reasonable expectation elicit strong neural responses (Dien et al, 2003;James et al, 2008;Vuust et al, 2009;Pearce et al, 2010;Kim et al, 2011). The ability of the brain to detect and respond to improbable events is thought to depend not only on mastery of complex rules that govern the event stream but also on the encoding of simple statistical relations (Aslin and Newport, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Repeated exposure to deviant chords in chord sequences did not influence the ERAN magnitude (Guo & Koelsch, 2015), suggesting that short-term experience could not modulate the early evoked responses such as the ERAN. A previous study demonstrated that conditional probabilities in Western music corpus were reflected in the ERAN even in nonmusicians, suggesting that the long-term musical knowledge is acquired by statistical learning (Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…The N400 could reflect transgressed endings of chord sequences in music (James, Cereghetti, Roullet, & Oechslin, 2015). The early right anterior negativity (ERAN), which was elicited by deviant chords embedded in chord progression in the same latency range of the ELAN, could reflect syntactic processes in music recognition (Kim, Kim, & Chung, 2011;Koelsch, Gunter, Friederici, & Schroger, 2000;Koelsch, 2009). Repeated exposure to deviant chords in chord sequences did not influence the ERAN magnitude (Guo & Koelsch, 2015), suggesting that short-term experience could not modulate the early evoked responses such as the ERAN.…”
Section: Introductionmentioning
confidence: 98%
“…With regard to violations of expectancies established on the basis of implicit knowledge, numerous neurophysiological studies have indicated that processing of music-syntactic expectancy violations is reflected electrically in an early anterior negativity that often has right-hemispheric weighting (the early right-anterior negativity, or ERAN; Koelsch et al, 2000;Leino et al, 2007;Carrión and Bly, 2008;Miranda and Ullman, 2007;Müller et al, 2010;Garza Villarreal et al, 2011;Kim et al, 2011;Kalda and Minati, 2012;Brattico et al, 2013;Koelsch et al, 2013;Sammler et al, 2013; for a review see Koelsch, 2012). ERAN effects have been shown in non-musicians, that is, in individuals who have implicit knowledge of music-syntactic regularities (although the ERAN has slightly larger amplitude in musicians than in non-musicians, e.g.…”
Section: Introductionmentioning
confidence: 99%